The Effectiveness of Life Skill Education-Based Digital Content to Improve Student Career Planning - Hani, Haris Yuftika; Mulawarman, Mulawarman; Eddy Wibowo, Mungin (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2021)
Career planning is one of important skill aspects taught to students through various methods. Most counselors tend to apply face to face method to teach it. Meanwhile, due to COVID-19 pandemic this method is truly difficult to be applied. For this reason, this studyattempted to examine the effectiveness of life skill education-based digital content to improve students’ career planning by involving 150 students. The results of analysis showed that students’ careerplanning successfully improved after the implementation of career guidance through life skill education-based digital content applied (t = -189.37, p = 0.01). Based on the results, life skill education based digital content is highly recommended to improve career planning in this COVID-19 pandemic